Comparison of TLR2/1, NF-ÐºB p105/50, NF-ÐºB p65, and TNF-Î± expressions in the macrophages between multibacillary leprosy patients with and without erythema nodosum leprosum signifying innate immune system activity - M. Yulianto Listiawan, - (Sanglah General Hospital, 2019)
Background: Erythema nodosum leprosum (ENL) is one of the complications in multibacillary (MB) leprosy. The cause, mechanism, and treatment of ENL remain highly problematic. Various studies have identified possible involvement of the innate immune system in the pathogenesis of ENL. Increased understanding of this mechanisms maybe useful for the management of leprosy. Objective: To compare the expression of Toll-like Receptor-2/1 (TLR2/1), Nuclear Factor Kapha Beta (NF-ÐºB) p105/p50, NF-ÐºB p65, Tumor Necrosis Factor-Î± (TNF-Î±) in the macrophages of MB patients with and without ENL as a marker of innate immune system involvement. Methods: Â This study is a cross-sectional study performed on 42 MB leprosy patients (21 with ENL and 21 without ENL) in the outpatient unit of Dr. Soetomo General Hospital from February to December 2010. Immunohistochemical staining method was conducted on all groups to determine the expression in macrophages of the dermis using the specific monoclonal antibody for TLR2/1, NF-ÐºBp105/p50, NF-ÐºBp65, and TNF-Î±. Statistical analysis was performed using Mann-Whitney U test. Result: There was a significant difference of TLR2/1, NF-ÐºBp105/p50, NF-ÐºBp65, and TNF-Î± expression in the dermis macrophages between the MB leprosy patients with ENL and without ENL. Conclusion: The innate immunity was activated in the ENL reaction of MB leprosy.